2010
DOI: 10.1007/s11739-010-0478-2
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vein occlusions: a review for the internist

Abstract: Retinal vein occlusion (RVO) is a disease that is often associated with a variety of systemic disorders including arterial hypertension, diabetes mellitus, dyslipidemia and systemic vasculitis. There are various types of RVO, categorized on the basis of the site of occlusion and on the type of consequent vascular damage. Central retinal vein occlusion (CRVO) is the most clinically relevant type of RVO. In addition to well-known classical risk factors, new thrombophilic factors have been investigated in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 47 publications
1
45
0
3
Order By: Relevance
“…Although it is recommended that a comprehensive cardiovascular risk assessment be performed in patients with retinal arterial and venous occlusions [5][6][7], a history of retinal venous or arterial occlusion is not formally included in these stroke risk assessment tools for patients with atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is recommended that a comprehensive cardiovascular risk assessment be performed in patients with retinal arterial and venous occlusions [5][6][7], a history of retinal venous or arterial occlusion is not formally included in these stroke risk assessment tools for patients with atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with retinal vascular occlusions often present to general practitioners or ophthalmologists, and have previously been associated with various cardiovascular risk factors [7][8][9][10][11][12][13], cerebral microembolisms [14], and cardiovascular events, including stroke and myocardial infarction [11,[15][16][17]. However, another study found that risk factor prevalence differed somewhat between patients with retinal and cerebral ischemia, indicating that there might be pathogenetic differences between retinal and cerebral ischemia [18].…”
Section: Introductionmentioning
confidence: 99%
“…hypertension, hyperlipidemia, diabetes mellitus or systemic vasculitis). 5,6 In addition to these well-known classical risk factors, hyperhomocysteinemia appears to play a significant role in the pathogenesis of this disease, 6 and is considered the most common "emerging" risk factor related to RVO. 7 Rubeosis iridis is a well-known complication of ischemic CRVO, which if not treated in time may lead to neovascular glaucoma (NVG).…”
Section: 3e5mentioning
confidence: 99%
“…In this issue of Internal and Emergency Medicine, Marcucci et al [5] provide an exhaustive review on the pathogenesis and management of RVO, with a particular focus on the role of the internist. The interaction between ophthalmologists and internists or vascular specialists is indeed crucial in the light of the main therapeutic goals for these patients.…”
mentioning
confidence: 99%
“…Based on the current evidence, Marcucci et al [5] propose a long list of diagnostic tests for this general work up, and have suggested potential therapeutic strategies.…”
mentioning
confidence: 99%